Can an internet-based program for the prevention and early intervention in eating disorders facilitate access to conventional professional healthcare?. (2nd September 2016) - Moessner, Markus; Minarik, Carla; Özer, Fikret; Bauer, Stephanie
Abstract: Background : The majorities of individual suffering from eating disorders do not seek or receive adequate professional treatment. Internet-based approaches promise to facilitate access to conventional healthcare by providing an easy-access, low-threshold contact. Aim : The current study investigated whether an Internet-based program for the prevention and early intervention for eating disorders (ProYouth) may contribute to the actual and intended uptake of professional care. Characteristics of individuals who seek help are explored as well as barriers to help-seeking. Method : The sample included 453 ProYouth participants who were surveyed three months after registration. Actual help-seeking behavior, intended help-seeking, potential help-seeking, and barriers to help-seeking were assessed. Results : Within three months of participation, 43 individuals (9.5%) took up treatment, 32 (7.8%) intended to start treatment, and 163 (43.1%) of the remaining reported that they would seek professional help in case of need (potential help-seeking). Approximately 50% of (potential) help-seekers stated that participation in ProYouth has changed their attitude towards help-seeking. Mental health literacy and shame/stigma were the most frequently mentioned barriers. Conclusions : This is the first study indicating that an online program for prevention and early intervention may serve as facilitator in accessing conventional healthcare.